Climate change in relation to agriculture - Camelia Slave; Ioana Vizireanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Climate change in Romania, will affect all sectors of the economy will lead to changes in vegetation periods and displacement the line between woods and meadows. Extreme weather events (storms, floods, droughts) will occur more frequently, and related risks and damages may become more significant. The areas affected by drought have expanded in the last decades the most exposed being in southeast and most of the country was affected by long lasting dry period. Together with floods, long periods of drought lead to significant economic losses in agriculture, transport, energy, water management, health and activity of households.
Keywords: 330; agriculture; climate; climate change; greenhouse environment